2015
DOI: 10.1111/maq.12152
|View full text |Cite
|
Sign up to set email alerts
|

Communicating “Evidence”: Lifestyle, Cancer, and the Promise of a Disease‐free Future

Abstract: In the era of evidence-based health care, conferences aimed at disseminating scientific knowledge perform an essential role in shaping policy and research agendas and transforming physician practice. Drawing on observations at two U.S. cancer prevention conferences aimed at knowledge translation, we examine the ways that evidence regarding the relationship between cancer and lifestyle is articulated and enacted. We show that characterizations of the evidence base at the conferences far outstripped what is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Hill and Hayes (2015) applied similar analysis to public health initiatives and associated campaigns encouraging patient 'awareness' of symptoms of cancer, and Topping et al (2013) explored how these practices locate the responsibility for late diagnosis with patients. A similar theme was taken up in other analyses of how cancer prevention approaches based around evidence-based medicine (Bell and Ristovski-Slijepcevic 2015), mathematical models to determine risk estimations for individuals (Holmberg and Parascandola 2010), or linking the risk of cancer to particular behaviours ) foreground individual responsibilities for risk management while giving 'minimal attention to the social and environmental context needed to achieve this' ).…”
Section: Individualising Responsibility For Riskmentioning
confidence: 95%
“…Hill and Hayes (2015) applied similar analysis to public health initiatives and associated campaigns encouraging patient 'awareness' of symptoms of cancer, and Topping et al (2013) explored how these practices locate the responsibility for late diagnosis with patients. A similar theme was taken up in other analyses of how cancer prevention approaches based around evidence-based medicine (Bell and Ristovski-Slijepcevic 2015), mathematical models to determine risk estimations for individuals (Holmberg and Parascandola 2010), or linking the risk of cancer to particular behaviours ) foreground individual responsibilities for risk management while giving 'minimal attention to the social and environmental context needed to achieve this' ).…”
Section: Individualising Responsibility For Riskmentioning
confidence: 95%
“…There has been extensive research relating to different aspects of this, that I cannot summarise fully here. However, various studies have shown that, for instance: recognising the causal link lifestyles make to chronic diseases, such as heart disease and cancer, is connected with responsibility and blame ascriptions for those diseases, including amongst physicians (Richards et al 2003 ; Bell and Ristovski-Slijepcevic 2015 ); emphasising the potential for lifestyle modifications to reduce risk of disease affects beliefs about control, blame, and responsibility (Sachs 1996 ; Brownell 1991 ; Alicke 2000 ); health policy that involves coercion or punishment is better accepted where those targeted are considered responsible for the relevant health-related behaviour (Branson et al 2012 ); notions of responsibility for disease may moderate the acceptability of using rewards (as well as penalties) as a means of treatment (Promberger et al 2011 ); cues about behavioural contributions to disease result in diminished willingness to provide financial support for healthcare costs (Gollust and Lynch 2012 ).…”
Section: Moralising Health and Responsibilitymentioning
confidence: 99%
“…As should thus be achingly clear to health geographers, they are not a distracting frivolity from the real biomedical spaces of global health, but rather crucial and alternative archetypal spaces where suffering and pleasure collide in complex ways that are too often antithetical to good health. They are also intensely political spaces, where commercial exigencies, vested interests and public health aspirations crash into the individual freedom to consume (see for example Bell and Ristovski-Slijepcevic 2015;Sanabria 2016). These spaces thus represent an uneasy addition to the architecture of global health, not just because of the financial entanglements between some of the 'commercial vectors of disease' and major global health players such as the Gates Foundation (McGoey 2015;Stuckler et al 2011), but also because they fundamentally destabilise the conceptual and moral foundations of the suffering slot.…”
Section: The Absent Spaces Of Global Healthmentioning
confidence: 99%